Ritual and symbolic communication in medieval Hungary under the Árpád Dynasty (1000-1301) - Zupka, Dušan, 1981- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2016)
In Rituals and Symbolic Communication in Medieval Hungary under the Árpád Dynasty (1000 - 1301) Dušan Zupka examines rituals as means of political and symbolic communication in medieval Central Europe, with a special emphasis on the rulers of the Árpád dynasty in the Kingdom of Hungary. Particular attention is paid to symbolic acts such as festive coronations, liturgical praises, welcoming of rulers ( adventus regis ), ritualised settlement of disputes, and symbolic rites during encounters between rulers. The power and meaning of rituals were understandable to contemporary protagonists and to their chroniclers. These rituals therefore played an essential role in medieval political culture. The book concludes with an outline of ritual communication as a coherent system.